The influence of above-ground herbivory on the response of arctic soil methanotrophs to increasing ch4 concentrations and temperatures - Rainer, Edda Marie; Seppey, Victor William Christophe; Hammer, Caroline; Svenning, Mette Marianne; Tveit, Alexander (Microorganisms, 2021)
Rising temperatures in the Arctic affect soil microorganisms, herbivores, and peatland vegetation, thus directly and indirectly influencing microbial CH 4 production. It is not currently known how methanotrophs in Arctic peat respond to combined changes in temperature, CH 4 concentration, and vegetation. We studied methanotroph responses to temperature and CH 4 concentration in peat exposed to herbivory and protected by exclosures. The methanotroph activity was assessed by CH 4 oxidation rate measurements using peat soil microcosms and a pure culture of Methylobacter tundripaludum SV96, qPCR, and sequencing of pmoA transcripts. Elevated CH 4 concentrations led to higher CH 4 oxidation rates both in grazed and exclosed peat soils, but the strongest response was observed in grazed peat soils. Furthermore, the relative transcriptional activities of different methanotroph community members were affected by the CH 4 concentrations. While transcriptional responses to low CH 4 concentrations were more prevalent in grazed peat soils, responses to high CH 4 concentrations were more prevalent in exclosed peat soils. We observed no significant methanotroph responses to increasing temperatures. We conclude that methanotroph communities in these peat soils respond to changes in the CH 4 concentration depending on their previous exposure to grazing. This “conditioning” influences which strains will thrive and, therefore, determines the function of the methanotroph community.